2006
DOI: 10.1097/01.shk.0000226340.25163.75
|View full text |Cite
|
Sign up to set email alerts
|

DIFFERENTIAL CONTRIBUTION OF N-METHYL-d-ASPARTATE AND NON-N-METHYL-d-ASPARTATE RECEPTORS IN THE INTERMEDIOLATERAL CELL COLUMN OF THE THORACIC SPINAL CORD TO SYMPATHETIC VASOMOTOR TONE DURING EXPERIMENTAL ENDOTOXEMIA IN THE RAT

Abstract: Although the rostral ventrolateral medulla maintains neurogenic vasomotor tone via glutamatergic excitation to sympathetic preganglionic neurons located at the intermediolateral cell column (IML) of thoracic spinal cord, the relative contribution of N-methyl-d-aspartate (NMDA) and non-NMDA receptors on IML neurons at rest or during endotoxemia remain unknown. The present study addressed this issue using a combination of physiological, pharmacological, and double-immunofluorescence approaches. Adult male Spragu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 29 publications
2
14
0
Order By: Relevance
“…Previous research has revealed that NR1 expression is upregulated during inflammation and plays an important role in maintaining the vasomotor tone in the intermediolateral cell column (IML) during endotoxemia (Poon et al, 2006). However, the mechanism underlying NMDAR expression is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has revealed that NR1 expression is upregulated during inflammation and plays an important role in maintaining the vasomotor tone in the intermediolateral cell column (IML) during endotoxemia (Poon et al, 2006). However, the mechanism underlying NMDAR expression is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that NR1 plays a crucial role in maintaining the vasomotor tone in the IML during endotoxemia (Poon et al, 2006). Furthermore, the upregulation of NR1 expression in the spinal cord plays an important role in the development of hyperalgesia after inflammation (Q.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true for postganglionic sympathetic neurons innervating the spleen, which substantially reduce tumor necrosis factor-a production from splenic macrophages during endotoxemia (Huston et al, 2006;Rosas-Ballina et al, 2008;Vida et al, 2011;Martelli et al, 2014). Catecholamines also promote protective cardiovascular effects during sepsis that partially counteract the severe hypotension and global tissue hypoxia that ensue (Jones et al, 1994;Poon et al, 2006). Augmentation of the endogenous sympathetic response may therefore provide an effective therapeutic intervention for patients suffering from this condition.…”
Section: Potential Significancementioning
confidence: 94%
“…Inhibition of preganglionic sympathetic neuron activation produces more severe hypotension and increases the mortality rate of endotoxemia (2,18,80). ACCs make an important contribution to this compensatory response because adrenal demedullation, adrenalectomy, adrenal denervation, and ligation of the adrenal vein are associated with more severe hypotension and higher mortality rates during endotoxemia (1)(2)(3)(4)18).…”
Section: Potential Significancementioning
confidence: 99%